Pengaruh Social Media Marketing, Discount Dan Brand Awareness Terhadap Keputusan Pembelian Produk Kosmetik Barenbliss Di Shopee - Adinda Frisilla; Puti Embun Sari (GLOBAL SCIENTS PUBLISHER, 2025)
This research aims to analyze the effect of social media marketing, discounts, and brand awareness on purchase decisions for Barenbliss cosmetic products on Shopee. The study uses a quantitative approach with data collected from 100 respondents through a structured questionnaire. The analysis employed multiple linear regression to determine the partial and simultaneous influence of the variables. The results show that social media marketing, discounts, and brand awareness significantly influence purchasing decisions, both individually and simultaneously. These findings suggest that strengthening digital marketing strategies and brand engagement can enhance consumer purchasing behavior.